Analyze The Influence of Family Labor and Looms on Production Results at The Woven Fabric Craft Center in Pringgasela Village: Analisis Pengaruh Tenaga Kerja Keluarga dan Alat Tenun Terhadap Hasil Produksi Pada Sentra Kerajinan Kain Tenun Desa Pringgasela - Nia Rahma Juniar; Helmy Fuadi; Sujadi, Sujadi (Economy and Finance Enthusiastic, 2023)
This study aims to analyze the influence of family labor and looms on production results in woven fabric craft centers in Pringgasela village. The research method used was a questionnaire as a data collection instrument. The sample for this study were 51 respondents who were owners or workers in the woven fabric craft industry in Pringgasela Village. The data used is primary data. The data analysis method used is multiple linear regression using the SPSS analysis tool. The results of the data analysis show that family labor has a positive and significant influence on production results in woven fabric craft centers. In addition, looms also have a positive and significant impact on production. Based on the results of testing the coefficient of determination, the R-Square value is 0.586, meaning that the variables of family labor and looms together affect the variable production result by 58.6%. While the remaining 41.4% is influenced by other variables outside this study. Follow-up recommendations from this research are to increase the training of family workers in more advanced weaving techniques and to promote the use of modern looms in these woven fabric craft centers.